Timelessness à la Leftow - Page, Ben (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
Brian Leftow has argued in significant detail for a timeless conception of God. However, his work has been interacted with less than one might expect, especially given that some have contended that divine timelessness should be put to death and buried. Further, the work that has critically interacted with Leftow does a very poor job at discrediting it, or so I will contend. As we shall see, the main reason for this is either because what is central to Leftow’s view is not affected by the objection, or because Leftow provides another way of getting his theory off the ground. Why, then, do so many objections miss the mark? I suspect it’s because many struggle to understand Leftow’s view and what is central to it. As such, one of the main goals of this paper will be to make Leftow’s account more accessible and to elucidate the main elements of the theory, whilst also providing responses to the main objections raised against his view. The overall result of this, I hope, will be a more fruitful examination of Leftow’s view in the future.